Elevated serum homocitrulline levels in patients with multiple sclerosis and its relationship with disease activity (Annals of Medical Research, 2022)
Aim: Multiple sclerosis (MS) is a demyelinating disease of central nervous system. Myelin basic protein (MBP) is the major protein in the structure of the myelin sheath, and the abnormal autoimmune response to MBP is related to the demiyelinization in MS. This autoimmune response is thought to be related to extensive post-translational modifications that may occur in the primary structure of MBP. Considering the role of post-translational modifications of MBP in the pathogenesis of MS, this study aimed to investigate the role of carbamylation in the pathogenesis of MS by measuring Hcit levels in patients with MS.Materials and Methods: This study included 80 patients with MS according to McDonald criteria by clinicians, and 60 healthy volunteers. Patients were divided into 2 groups as relapsing-remitting multiple sclerosis (RRMS) (n=44) and secondary progressive MS (SPMS) (n=36) according to Expanded Disability Status Scale (EDSS) score evaluated by clinicians. Serum homocitrulline and lysine levels were measured with validated tandem mass spectrometric method.Results: Serum Hcit levels in patients with MS were statistically significantly higher than the healthy controls. Comparison of MS subgroups according to Hcit levels showed that serum Hcit levels were higher in patients with SPMS than in patients with RRMS. Serum Hcit levels were positively correlated with EDSS and disease duration.Conclusion: Serum Hcit levels were significantly elevated in patients with MS. Moreover, there was a correlation between serum Hcit levels and disease activity and duration of disease.
Keywords: Multiple sclerosis; Homocitrulline; Myelin basic protein; Post-translational modifications; Inflammation